Perencanaan Bahasa Pertama Terhadap Pemerolehan Bahasa Kedua - Sabrina, Reno Mardhatillah (Orasi: Jurnal Ilmu Politik dan Sosial, 2025)
The purpose of this study was to look at the problems that occur in the development of the second language acquisition of children by parents who are reluctant to teach regional languages ​​to their children. Higher community prestige towards Indonesian and foreign languages ​​causes a lack of speaker loyalty to the local language. This is caused by a lack of awareness of parents to place regional languages ​​as the mother tongue of their children. The results of this study indicate that there is an impact arising from the selection of mother tongue on the development of the language of the two children. Children who are invited to speak Indonesian from birth tend to find it difficult to adjust language when interacting with their friends. As a result, he became a little mastered or could be said to be non-multilingual.